2019
DOI: 10.1128/jcm.01307-18
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas Biology and Its Application to Infectious Diseases

Abstract: Infectious diseases remain a global threat contributing to excess morbidity and death annually, with the persistent potential for destabilizing pandemics. Improved understanding of the pathogenesis of bacteria, viruses, fungi, and parasites, along with rapid diagnosis and treatment of human infections, is essential for improving infectious disease outcomes worldwide. Genomic loci in bacteria and archaea, termed clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (Cas) prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 59 publications
(55 reference statements)
0
121
0
2
Order By: Relevance
“…The success of fecal microbiome transplants may someday require companion, real-time metagenomic characterization of donor stool as well as post-microbiome engraftment analyses [78]. Similarly, phage therapy, with or without CRISPR-Cas9 strategies, to combat highly antimicrobial resistant bacteria may require metagenomic analyses to assess efficacy [79,80].…”
Section: Additional Future Directionsmentioning
confidence: 99%
“…The success of fecal microbiome transplants may someday require companion, real-time metagenomic characterization of donor stool as well as post-microbiome engraftment analyses [78]. Similarly, phage therapy, with or without CRISPR-Cas9 strategies, to combat highly antimicrobial resistant bacteria may require metagenomic analyses to assess efficacy [79,80].…”
Section: Additional Future Directionsmentioning
confidence: 99%
“…143,144 CRISPR (clustered regularly inter-spaced short palindromic repeats) and the related CRISPRassociated (Cas) proteins have also been investigated as potential therapeutics for highly resistant gram-negative infections specifically targeting bla NDM-1 -producing organisms. 145,146 Furthermore, there has been a resurgence of interest in the use of phage (viruses that lyse bacterial targets). A recent systematic review has concluded that phage therapy is effective and safe based on the limited publications to date, but more data are needed as challenges in manufacturing and the regulatory process remain.…”
Section: Inhaled Antibioticsmentioning
confidence: 99%
“…applied to design antimicrobials working by targeting specic DNA sequences related to antibiotic resistance, biolm formation and virulence. [165][166][167] These CRISPR-Cas antimicrobials function by destroying the DNA through chromosomal cleavage by using the RNA-guided nuclease Cas9, selectively killing the target DNA-harbouring bacteria. Although recent studies have proven the effectiveness of CRISPRs, the lack of an efficient delivery vehicle remains to be one of the major barriers for translating CRISPR-Cas system into a suitable antimicrobial agent for human medicine.…”
Section: Perspectives Of Lchnpsmentioning
confidence: 99%